Chapter Dante's Journey Through Our Lives: Reading La Commedia in Post-Apartheid South Africa - Trento, Giovanna (Studi e saggi, 2021)
By appropriating the notions of journey and exile-that are at the core of Dante's life and work-the texts we are examining in this publication are able to refer to/relate to the conditions of exile, exclusion, and segregation that were proper to Apartheid and still affect post-Apartheid South Africa. The works of Erich Auerbach and Franco Fortini (who unexpectedly in the 1980s accepted an invitation of the University of the Witwatersrand in Johannesburg) help us to read these texts within the wider frame of 20th and early 21st interpretations and rereading of Dante's Commedia.